Exploration of the Challenges in Adopting Smart Farming Among Smallholder Farmers: A Qualitative Study - Dayang Siti Norhafiza, Abang Ahmad; Fazleen, Abdul Fatah; Abdul Rahman, Saili; Jamayah, Saili; Nur Masriyah, Hamzah; Rumaizah, Che Md Nor; Zubaidah, Omar; Mohamed, Ghali (SEMARAK ILMU PUBLISHING, 2024)
Applications of smart farming have been introduced as a way out of various production issues in the agriculture sector, especially during the occurrence of COVID-19. Several technical studies have also been done to develop the modules that meet the operational requirements in Malaysia and determine their benefits and impacts on farmers. Despite the availability of smart farming technologies and their benefits to farmers’ productivity and profitability, adoption of smart farming among Malaysian farmers, especially in rural areas, remains a challenge. Therefore, a qualitative study among farmers in Sarawak and Sabah was conducted to determine the challenges that arise with the adoption of smart farming technologies. The results highlighted that farmer faced challenges in regard to the high startup cost of technology, lack of expertise and knowledge on technologies, connectivity and access in rural areas, farm size, and governmental support. In practice, this study also discussed the challenges of adopting smart farming mentioned by participants and some possible solutions for future attention.